Impact of perinatal and repeated maternal common mental disorders on educational outcomes of primary school children in rural Ethiopia: population-based cohort study. Issue 6 (November 2019) - Mekonnen, Habtamu; Medhin, Girmay; Tomlinson, Mark; Alem, Atalay; Prince, Martin; Hanlon, Charlotte
Abstract : Background: There have been no studies from low- or middle-income countries to investigate the long-term impact of perinatal common mental disorders (CMD) on child educational outcomes. Aims: To test the hypothesis that exposure to antenatal and postnatal maternal CMD would be associated independently with adverse child educational outcomes in a rural Ethiopian. Method: A population-based birth cohort was established in 2005/2006. Inclusion criteria were: age between 15 and 49 years, ability to speak Amharic, in the third trimester of pregnancy and resident of the health demographic surveillance site. One antenatal and nine postnatal maternal CMD assessments were conducted using a self-reporting questionnaire, validated for the local use. Child educational outcomes were obtained from the mother at T 1 (2013/2014 academic year; mean age 8.5 years) and from school records at T 2 (2014/2015 academic year; mean age 9.3 years). Results: Antenatal CMD (risk ratio (RR) = 1.06, 95% CI 1.05–1.07) and postnatal CMD (RR = 1.07, 95% CI 1.06–1.09) were significantly associated with child absenteeism at T 2 . Exposure to repeatedly high maternal CMD scores in the preschool period was not associated with absenteeism after adjusting for antenatal and postnatal CMD. Non-enrolment at T 1 (odds ratio 0.75, 95% CI 0.62–0.92) was significantly but inversely associated with postnatal maternal CMD. There was no association between maternal CMD and child academic achievement or drop-out. Conclusions: Our findings support the hypothesis of a critical period for exposure to maternal CMD for adverse child outcomes and indicate that programmes to enhance regular school attendance in low-income countries need to address perinatal maternal CMD. Declaration of interest: None.